The Influence of Macroeconomic News on Currency Exchange Rates in Indonesia 2018-2023 - Pranoto, Darmansyah Hegi; Suherman, Ujang; Pranata, Rengga Madya (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to explain the cause of the IDR exchange rate experiencing high fluctuations during 2018-2023 using monthly data. To determine whether macroeconomic news affects the IDR exchange rate, this study employs the Ordinary Least Square (OLS) model. In addition, this study aims to determine what macroeconomic news affects fluctuations in the IDR exchange rate. The main findings of the research results show that search interests related to macroeconomic news simultaneously affect the IDR exchange rate, but partially six of the eleven search interests related to macroeconomic news affect exchange rate fluctuations. In addition, the mean value which is greater than the median value on the dependent variable indicates that during the study period the IDR exchange rate tended to depreciate against the USD. Studies like this are still rare in Indonesia, making this research a valuable addition to financial management education. The researcher hopes that it can be developed further with other search interests that can affect and predict the movement of the IDR exchange rate.